Electrospun polycaprolactone/hydroxyapatite/ZnO nanofibers as potential biomaterials for bone tissue regeneration - Shitole, Ajinkya A.; Raut, Piyush W.; Sharma, Neeti; Giram, Prabhanjan; Khandwekar, Anand P.; Garnaik, Baijayantimala (Journal of Materials Science-Materials In Medicine, 2019)
Fabricating a bioartificial bone graft possessing structural, mechanical and biological properties mimicking the real bone matrix is a major challenge in bone tissue engineering. Moreover, the developed materials are prone to microbial invasion leading to biomaterial centered infections which might limit their clinical translation. In the present study, biomimetic nanofibrous scaffolds of Poly -caprolactone (PCL)/nano-hydroxyapatite (nHA) were electrospun with 1wt%, 5wt%, 10wt%, 15wt% and 30wt% of zinc oxide (ZnO) nanoparticles in order to understand the optimal concentration range of (ZnO) nanoparticles balancing both biocompatibility and osteoregeneration. The developed nanofibrous scaffolds were successfully characterized using scanning electron microscopy (SEM), transmission electron microscopy (TEM), energy dispersive X-ray analysis (EDAX), contact angle, fourier transform infrared spectroscopy (FTIR), wide-angle X-Ray diffraction (WAXD), brunaueremmett Teller (BET) surface area and tensile testing. Biocompatibility of the developed scaffolds at in vitro level was evaluated by culturing MG-63 cells and investigating the impact on cell viability, proliferation, protein adsorption, alkaline phosphatase (ALP) activity and biomineralization. The PCL/nHA scaffolds exhibited a 1.2-fold increase in cell viability and proliferation, while incorporation of ZnO nanoparticles to PCL/nHA imparted antimicrobial activity to the scaffolds with a progressive increase in the antimicrobial efficacy with increasing ZnO concentration. The results of cell viability were supported by ALP activity and mineralization assay, wherein, PCL/nHA/ZnO scaffolds showed higher ALP activity and better mineralization capacity as compared to pristine PCL. Although, the PCL/nHA/ZnO scaffolds with 10, 15 and 30wt% of ZnO particles exhibited superior antimicrobial efficacy against both gram-negative (E. coli) and gram-positive (S. aureus) bacteria, a significant decrease in the cell viability and mechanical properties was observed at higher concentrations of ZnO namely 15 and 30%. Amongst the various ZnO concentrations studied optimal cell viability, antimicrobial effect and mechanical strength were observed at 10wt.% ZnO concentration. Thus, the present study revealed that the biomimetic tri-component PCL/nHA/ZnO scaffolds with ZnO concentration range of10% could be ideal for achieving optimal biocompatibility (cell proliferation, biomineralization, and antimicrobial capacity) and mechanical stability thus making it a promising biomaterial substrate for bone tissue regeneration. [GRAPHICS] .

LHRH-conjugated, PEGylated, poly-lactide-co-glycolide nanocapsules for targeted delivery of combinational chemotherapeutic drugs Docetaxel and Quercetin for prostate cancer - Shitole, Ajinkya A.; Sharma, Neeti; Giram, Prabhanjan; Khandwekar, Anand; Baruah, Meghna; Garnaik, Baijayantimala; Koratkar, Santosh (Materials Science & Engineering C-Materials for Biological Applications, 2020)
One of the major challenges in effective cancer chemotherapy is the severe systemic cytotoxicities of anticancer drugs on healthy tissues. The present study reports chemically modified polymeric nanocapsules (NCs) encapsulating combination of chemotherapeutic drugs Docetaxel (DTX) and Quercetin (QU) for its active targeting to prostate cancer (PCa). The active targeting was achieved by conjugating Luteinizing-hormone-releasing hormone (LHRH) ligand to poly-lactide-co-glycolide (PLGA) using polyethylene glycol (PEG) as a spacer. The structure of the conjugates was characterized and confirmed using H-1 NMR and ATR-FTIR. The drug encapsulated NCs showed a homogenous size distribution with their size ranging between 120 and 150 nm, and exhibited a negative zeta potential in the range of - 20 to - 40 mV. The in vitro release studies highlighted the sustained drug release pattern from the respective NCs; while the PEG coating to polymeric NCs provided serum stability to the NCs. The in vitro biological evaluation of the NCs was conducted using PC-3 and LNCaP cell lines. The results of the cellular uptake studies showed a significantly higher untake of the LHRH targeted NCs, while the LHRH-targeted-PEGylated DTX: QU NCs exhibited higher caspase-3 activity. The cell viability assay results showed the enhanced cell inhibition activity of the combinatorial DTX: QU when compared to individual DTX. Further, higher cell cytotoxicity was achieved by LHRH-targeted DTX: QU NCs as compared to their free-form or non-targeted NCs. Finally, the results of in vivo tumor localization and in vivo antitumor activity studies complimented and upheld the in vitro results, demonstrating the beneficial role of PLGA-PEG-LHRH NCs encapsulating combination of DTX and QU in combating prostate cancer (PCa).
Keywords: Active targeting; Anticancer; Controlled release; EPR effect; Hydrophobic; Prostate

Poly (vinylpyrrolidone)-iodine engineered poly (epsilon-caprolactone) nanofibers as potential wound dressing materials - Shitole, Ajinkya A.; Raut, Piyush; Giram, Prabhanjan; Rade, Priyanka; Khandwekar, Anand; Garnaik, Baijayantimala; Sharma, Neeti (Materials Science & Engineering C-Materials for Biological Applications, 2020)
Facilitating the process of wound healing and effective treatment of wounds remains a serious challenge in healthcare. Wound dressing materials play a major role in the protection of wounds and in accelerating the natural healing process. In the present study, novel core/shell (c/s) nanofibrous mats of poly(vinyl pyrrolidone)-iodine (PVPI) and polycaprolactone (PCL) were fabricated using a co-axial electrospinning process followed by their surface modification with poly-L-lysine. The developed nanofibrous mats were extensively characterized for their physicochemical properties using various analytical techniques. The core/shell structure of the PVP-I/PCL nanofibers was confirmed using TEM analysis. The PVP-I release studies showed an initial burst phase followed by a sustained release pattern of PVP-I over a period of 30 days. The developed nanofibers exhibited higher BSA and fibrinogen adsorption as compared to pristine PCL. Cytotoxicity studies using MTT assay demonstrated that the PVP-I/PCL (c/s) nanofibers were cytocompatible at optimized PVP-I concentration (3 wt%). The PCL-poly-L-lysine and PVP-I/PCL-poly-L-lysine nanofibers exhibited higher cell viability (24.2% and 21.4% higher at day 7) when compared to uncoated PCL and PVP-I/PCL nanofibers. The PVP-I/PCL nanofibers showed excellent antimicrobial activity against both Gram-positive (S. aureus) and Gram-negative (E. coli) bacteria. The inflammatory response of Mouse RAW 264.7 macrophage cells towards the nanofibers was studied using RTPCR. It revealed that the pro-inflammatory cytokines (TNF-alpha and IL-1 beta) were significantly upregulated on PCL nanofibers, while their expression was comparatively lower on poly-L-lysine coated PCL or PVP-I/PCL(c/s) nanofibers. Overall, the study highlights the ability of poly-L-lysine coated PVP-I/PCL (c/s) nanofibers as potential wound dressing materials effectively facilitating the early stage wound healing and repair process by virtue of their selective modulation of inflammation, cell adhesion and antimicrobial properties.
Keywords: biodegradable; Controlled release; Core/shell; electrospinning; scaffolds; tissue engineering